La fabrique des écoliers, ou l'enfance enfermée - Henri Louis Go (Recherches en Éducation)
Following on from the asylums of the early 19th century, the school form as it materialized in the republican school system at the end of the 19th century made it possible to lock up part of the population: childhood was thus subjected to jailers who practiced social orthopedics. The school's promise of socializing and educating children turned out to be, in its historical construction, a deception. The confinement of school is thus a demarcation of being, a « putting in its place » of the pupil. The world does not enter the classroom, which remains desperately empty. What, then, are we to do in the classroom, if we are only to do what we do? For Arendt, the institution of school is supposed to stand between the family and the world, as a transition, because the institution of school is part of the pre-political sphere, and we can't pretend to forge a project of political transformation by acting on the newcomers: children can't and shouldn't take part in the world. Classical schooling is therefore the first act in a process of alienation that dispossesses each individual of his or her own existence through institutions of confinement. The republican idea is linked to an educational model that sees the government of children as a factory of consenting, consensual passivity. Opened in 1934 on the Pioulier hill in Vence, the École Freinet is a conservatory for children. But this school is neither an enclosed space « protected from outside noise », nor a merely intermediary space where the world would only enter « represented ». It's an alternative to the misery that weighs heavily on schoolchildren.